PENGGUNAAN JENIS DAN KONSENTRASI PATI SEBAGAI BAHAN DASAR EDIBLE COATING UNTUK MEMPERTAHANKAN KESEGARAN BUAH JAMBU CINCALO (Syzygium samarangense [Blume] Merr. & L.M. Perry) SELAMA PENYIMPANAN - Sitti Nurul Aini; Kusmiadi R; Napsiah Mey (Universitas Trilogi, 2019)
Cincalo wax apple is perrisible which is easily damaged due to fungus activity, thus shortening the shelf life of the fruit. The addition of starch and ginger extract is expected to inhibits fungus growth. The aims of this study is to determine the effect of edible coating on starch types and concentration to maintain cincalo wax apple fruit. This study was conducted at the Agrotechnology Laboratory and at the Tua Tunu village, used a Single Completely Randomized Design (CRD) there were 7 treatments which were the types of starch consisting of P0 = no treatment, P1 = canna starch 2%, P2 = canna starch 3%, P3 = starch canna 4%, P4 = 2% cassava starch, P5 = 3% cassava starch, P6 = 4% cassava starch. The results showed that the treatments of edible coating on starch had no significant effect on the obserrved variables, but vitamin C had a very significant effect on the 3th day of storage. Keywords: cincalo wax apple, damage, edible coating, respiration, starch